PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN SEKTOR BARANG KONSUMEN NON-PRIMER YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2021-2024 - Putri, Azizah Syafira; Afif, M. Nur; Melani, Maria Magdalena (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the impact of company size, profitability, and leverage on corporate social responsibility (CSR) disclosure in non-primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. Secondary data were obtained from the financial statements and sustainability reports of sample companies. Purposive sampling was used as the sampling method, resulting in 21 companies and 84 observations. Data analysis was conducted using panel data regression with EViews 12 software. The results partially indicate that company size, profitability, and leverage do not have a significant effect on CSR disclosure. This finding suggests that CSR disclosure decisions in this sector may be more strongly influenced by non-financial or strategic factors than solely financial indicators. The implications of this study enrich the literature on CSR and provide insights for companies and regulators regarding the importance of considering other factors in promoting CSR transparency. Keywords: Firm Size, Profitability, Leverage, Corporate Social Responsibility (CSR) Disclosure, Consumer Cyclical Sector.